Prenatal exposure to polybrominated diphenyl ethers and BMI Z-scores from 5 to 14 years - Allison Kupsco; Andreas Sjödin; Whitney Cowell; Richard Jones; Sharon Oberfield; Shuang Wang; Lori A. Hoepner; Dympna Gallagher; Andrea A. Baccarelli; Jeff Goldsmith; Andrew G. Rundle; Julie B. Herbstman (BMC, 2022)
Abstract Background Polybrominated diphenyl ethers (PBDEs) are flame-retardant compounds widely used in household products until phase out in 2004. PBDEs are endocrine disruptors and are suggested to influence signaling related to weight control. Prenatal exposures to PBDEs may alter childhood adiposity, yet few studies have examined these associations in human populations. Methods Data were collected from a birth cohort of Dominican and African American mother-child pairs from New York City recruited from 1998 to 2006. PBDE congeners BDE-47, − 99, − 100, and − 153 were measured in cord plasma (ng/μL) and dichotomized into low (< 80th percentile) and high (>80th percentile) exposure categories. Height and weight were collected at ages 5, 7, 9, 11, and an ancillary visit from 8 to 14 years (n = 289). Mixed-effects models with random intercepts for participant were used to assess associations between concentrations of individual PBDE congeners or the PBDE sum and child BMI z-scores (BMIz). To assess associations between PBDEs and the change in BMIz over time, models including interactions between PBDE categories and child age and (child age)2 were fit. Quantile g-computation was used to investigate associations between BMIz and the total PBDE mixture. Models were adjusted for baseline maternal covariates: ethnicity, age, education, parity, partnership status, and receipt of public assistance, and child covariates: child sex and cord cholesterol and triglycerides. Results The prevalence of children with obesity at age 5 was 24.2% and increased to 30% at age 11. Neither cord levels of individual PBDEs nor the total PBDE mixture were associated with overall BMIz in childhood. The changes in BMIz across childhood were not different between children with low or high PBDEs. Results were similar when adjusting for postnatal PBDE exposures. Conclusions Prenatal PBDE exposures were not associated with child growth trajectories in a cohort of Dominican and African American children.